In vitro antimicrobial activity of the triantibiotic paste, according to the time of application and storage - Carla Román-Inoñan; Victor Chumpitaz-Cerrate; Lesly Chávez-Rimache; César Franco-Quino; Carlos Erazo-Paredes (Editorial Ciencias Médicas, 2023)
Introduction: Intracanal medication with antibiotics is used to ensure the success of treatments. However, no studies evaluating the efficacy of triantibiotic paste after several hours of preparation have been reported. Objective: To evaluate the antimicrobial activity of the triantibiotic paste against Enterococcus faecalis, according to the time of application and storage of the components used for its preparation. Methods: An experimental in vitro study was carried out in the microbiology laboratory of Universidad Nacional Mayor de San Marcos. The sample consisted of three colonies of Enterococcus faecalis, formed in bile-esculin agar. On three specific days (0, 14 and 28), the antimicrobial activity of the conventional (ciprofloxacin/metronidazole/minocycline) and modified (cefaclor/metronidazole/minocycline) paste was evaluated, measuring (mm) the inhibition zones. The freshly obtained components were used to prepare the paste on day 0, and the stored components (powdered antibiotics kept in amber glass bottles at room temperature) were used on days 14 and 28. Two interventions were performed on each specific day (morning and afternoon). Freshly prepared pastes were used in the morning (immediate application), while pastes stored for 6 hours (delayed application) were used in the afternoon. Results: On day 0, it was found that the modified triantibiotic paste of immediate application had higher antimicrobial activity than the one of delayed application (p = 0.046). On day 28, the conventional triantibiotic paste for immediate application showed higher antimicrobial activity than that for delayed application (p = 0.049). Pasta prepared with fresh components (day 0) had higher antimicrobial activity than pasta prepared with components stored for 14 and 28 days. Conclusions: The application time of the triantibiotic paste and the storage times of the components could influence the antimicrobial activity for the eradication of Enterococcus faecalis.